Damages caused by Euxesta stigmatias on carrot roots in commercial seed field - França, Félix Humberto; Vecchia, Paulo Tarcísio Della (Pesquisa Agropecuaria Brasileira, 2014)
Euxesta stigmatias Loew, 1868 (Diptera: Otitidae: Ulidiinae), larvae were found causing parcial or total destruction on the top of the carrot (Daucus carota L.) roots in a seed field. The damages can delay the plant development and cause the plant death. The insect was studied in the laboratory. The average number of larvae per root, and the description of larvae, pupae and adults are presented.